CROATIAN PROFESSORS IN RUSSIAN UNIVERSITIES IN 1870-1880-th - A. N. Ptitsyn (Гуманитарные и юридические исследования)
The article studies research and teaching activities of Croatian scientists B. Bogishich and V. Yagitch working in Novorossiysk (in Odessa) and St. Petersburg Universities in the last third of the 19th century.